Potential of Cinnamomum burmanni Leaf Extract as an Exogenous Antioxidant and Spermatoprotective for Rattus norvegicus L. Exposed to Polystyrene Nanoplastics - Nurbani, Farah Annisa; Pramudya, Manikya; Safitri, Maya; Sugiharto; Aunurohim; Hayati, Alfiah; Septiani, Adiibtia; Dewi, Putri Alicia; Nashrulloh, Allam Thoriq; Vuanghao, Lim (HAYATI Journal of Biosciences, 2025)
Polytyrene nanoplastics (NPs) (